Almost sure stability criterion for continuous-time linear systems with uniformly distributed uncertainty. (March 2023) - Cong, Shen
Abstract: Assuming the uncertain parameter of a linear polytopic system to be uniformly distributed, we can prove that the system is almost sure exponentially stable if and only if its averaging system is stable. Computing the mathematical expectation of the state-transition matrix and characterizing the martingale structure embedded in its variance is the key for deriving this stability criterion.